2009
DOI: 10.4238/vol8-2gmr576
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of olive cultivars using amplified fragment length polymorphism markers

Abstract: ABSTRACT. We sampled six olive cultivars (Tavli Sati, Sati, Gorvela, Sacakli Otur, Butko, and Otur) from Coruh Valley, located in the northeast part of Turkey, and characterized them using amplified fragment length polymorphism (AFLP) markers. Some morphological and biochemical characteristics are also determined. Six AFLP primer combinations were used for molecular characterization and 66 AFLP markers were obtained. Six olive cultivars were classified into two major clusters using UPGMA clustering analysis; c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 13 publications
(14 reference statements)
2
16
0
2
Order By: Relevance
“…The results indicated that the 96 olive genotypes possessed a high-level of genetic variation. The genetic similarity values found in our study are comparable to the values previously found in other studies for the identification of Turkish olive genotypes using the AFLP [101], SSR [36], [44], and SRAP [36] markers. Isık et al [36] investigated the genetic diversity in 66 Turkish olive varieties using SSR markers.…”
Section: Discussionsupporting
confidence: 90%
“…The results indicated that the 96 olive genotypes possessed a high-level of genetic variation. The genetic similarity values found in our study are comparable to the values previously found in other studies for the identification of Turkish olive genotypes using the AFLP [101], SSR [36], [44], and SRAP [36] markers. Isık et al [36] investigated the genetic diversity in 66 Turkish olive varieties using SSR markers.…”
Section: Discussionsupporting
confidence: 90%
“…Randomly amplified polymorphic DNA (RAPD) markers were the first molecular markers used to identify olive cultivars (Bogani et al, 1994). Later, amplified fragment length polymorphism (AFLP) markers were found to be useful for the assessment of genetic diversity between olive cultivars, wild genotypes, and Olea species (Angiolillo et al, 1999;Owen et al, 2005;Ercisli et al, 2009). Simple sequence repeat (SSR) markers are another choice of marker technology for the characterization of olive genotypes and a considerable number of SSR markers have been developed for the olive genome in recent years (e.g., Rallo et al, 2000;Sefc et al, 2000;Ipek et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Morphological and pomological characteristics of common Turkish olive cultivars were previously determined by Canozer (1991). Genetic variation among some Turkish olive cultivars was analyzed using DNA based molecular markers (Owen et al, 2005;Ozkaya et al, 2006;Ercisli et al, 2009;Ipek et al, 2009).…”
Section: Introductionmentioning
confidence: 99%